The total number of Leydig and Sertoli cells in the testes of men across various age groups – a stereological study - Petersen, Peter M (J Anat, 2015)
The aim of this study was to estimate the total number of Sertoli and Leydig cells in testes from male subjects across the human lifespan, using an optimized stereological method for cell-counting. In comparison with many other organs, estimation of the total cell numbers in the testes is particularly sensitive to methodological problems. Therefore, using the optical fractionator technique and a sampling design specifically optimized for human testes, we estimated the total number of Sertoli and Leydig cells in the testes from 26 post mortem male subjects ranging in age from 16 to 80 years. The mean unilateral total number of Sertoli cells was 407 × 10(6) [range: 86 × 10(6) to 665 × 10(6), coefficient of variation (CV) = 0.33], and the mean unilateral total number of Leydig cells was 99 × 10(6) (range: 47 × 10(6) to 245 × 10(6), CV = 0.48). There was a significant decline in the number of Sertoli cells with age; no such decline was found for Leydig cells. Quantitative stereological analysis of post mortem tissue may help understand the influence of age or disease on the number of human testicular cells.